Benefícios sociais da política de incentivos à cultura do mamão no estado do Ceará - Quintino, Heliana Mary da Silva (2007)
The objective of this study is to analyze it benefit social generated by the Government's incentives of Ceará to the producing of papaya of the State, in the period from 2001 to 2006, considering as theoretical base the models of simultaneous equations and of approach of Marshall's economical surplus. For so much, a series of annual data was used, considered for the period from 1973 to 2006, obtained the General office of the Agriculture and Livestock of Ceará close to — SEAGRI/CE, Institute of Research and Economical Strategy of Ceará — IPECE and the Institute of Applied Economical Research — IPEA. With base in the estimate of the offer equations and demand was possible to measure the rude monetary amounts gained by the society promoted by the actions implemented through the Project Fruits of Ceará. The results pointed that the papaya offer in the State has an elasticity-price discharge, however the decreasing behavior of the same ones, mainly, in the period former-post to the incentives (a medium fall 285,71%), it didn't affect it growth: there was a highly significant medium increase, of the order of 573,27%. the reduction in the prices and the parallel increase in the offer was responsible for an elevation in the social well-being. The economical surplus totaled a joined value of R$ 3.163.045,86 and per capita of R$ 0,39 when considered starting from the increase in the offer with the respective reduction in the medium costs of production. Though, when considered through the enlargement of the offer at annual medium costs constant, the amount attaché was R$ 1.776.805,12 and per capita of R$ 0,22. This results in a difference of 178,02% in terms of benefit and reveals the importance of actions returned for the reduction in the production as form of stimulating the development of the horticulture in the State of Ceará. Its benefit social through the generation of jobs it totaled R$ 4.690.042,10, being R$ 2.814.025,25 corresponding to indirect jobs and R$ 1.876.016,84 corresponding to direct jobs. Additionally, the producers noticed an increment in their incomes medium per capitas of 167,05% and joined of 282,74% with the commercialization of the papaya. Like this, it is ended that the government incentives of the State of Ceará, with their several fomentation programs to the economical segment of the horticulture projected the market of papaya from Ceará, generating a growing tendency of the production as well as of the number of jobs in the producing areas.